Analisis Struktur Teks Negosiasi dalam Aplikasi Tiktok Shop sebagai Bentuk Alternatif Bahan Ajar Siswa SMA Kelas X: The Analysis of Negotiation Text Structure in the Tiktok Shop Application as an Alternative Form of Teaching Material for Grade X High School Students - Arifah, Siti; Afifah, Siti (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2025)
Negotiation is not only closely related to activities in the market between sellers and buyers, but negotiation activities can occur in the form of visual content on social media, especially TikTok social media, which will be the object of this study. Thus, the purpose of this study is to provide a detailed description of the structure of negotiation texts in TikTok social media content as an alternative form of teaching materials for high school students in grade X. This study uses a qualitative research approach with a descriptive type of research because the results of the data that have been obtained are in the form of narratives or expressions that are conveyed verbally between speakers and TikTok shop social media interlocutors so that this study produces a finding about the structure of the negotiation text. This study went through three stages in data collection techniques: documentation techniques by downloading some content on TikTok social media, continued with listening techniques, and note-taking techniques. The results of this study relate to the structure of the negotiation text, including three criteria elements: opening, content, and closing. Negotiation texts have advantages and disadvantages. Not all forms of social interaction related to negotiation meet the completeness of the negotiation text structure. Thus, this study is expected to open comparable studies with different objects to contribute to the advancement of education in Indonesia.